Study on possible role of CYP1A1, GSTT1, GSTM1, GSTP1, NAT2 and ADRB2 genes polymorphisms in bronchial asthma development in children - Tatarskyy, P.F.; Chumachenko, N.G.; Kucherenko, A.M.; Gulkovskyi, R.V.; Arabskaya, L.P.; Smirnova, O.A.; Tolkach, S.I.; Antipkin, Yu.G.; Livshits, L.A. (Вiopolymers and Cell, 2011)
Aim. To study the association of polymorphisms of the enzymes genes CYP1A1 (T6235C), first phase, and NAT2 (Ñ481Ò, G590A, G857A), GSTM1 («0»), GSTT1 («0») and GSTP1 (A313G), second phase of the detoxication system, as well as the ADRB2 (C79G) gene variants with the development of bronchial asthma in children. Methods. Polymorphic variants were analyzed using PCR followed by RFLP analysis in 86 healthy individuals and in 114 patients with clinical diagnosis of bronchial asthma. Results. The frequency of gene polymorphic variants of the enzymes of first and second phases of detoxification system as well as the ADRB2 gene was established in the children with bronchial asthma and healthy individuals. Conclusions. Ðolymorphic variants of the genes NAT2 (481Ò), GSTP1 (313G) and ADRB2 (79G) and their combinations in geno- type were observed more frequently in the patients with bronchial asthma comparing to the control group, which indicates their invol- vement in the pathogenesis of asthma in children Keywords: bronchial asthma, detoxication system, 2-adrenoreceptor gene, polymorphism, combined genotype. Мета. Дослідити зв’язок поліморфних варіантів генів ферментів першої – CYP1A1 (T6235C) та другої – NAT2 (С481Т, G590A, G857A), GSTM1 («0»), GSTT1 («0») і GSTP1 (A313G) фаз системи детоксикації, а також гена ADRB2 (C79G) з розвитком бронхіальної астми (БА) у дітей. Методи. Поліморфні варіанти вивчали за допомогою ПЛР та ПДРФ-аналізу у 86 здорових індивідів та у 114 пацієнтів з клінічним діагнозом БА. Результати. Встановлено частоту поліморфних варіантів генів ферментів першої і другої фаз системи детоксикації, а також гена ADRB2 у хворих на БА дітей та у здорових індивідів. Висновки. Поліморфні варіанти генів NAT2 (481Т), GSTP1 (313G) і ADRB2 (79G) та їхні комбінації в генотипі частіше спостерігаються серед пацієнтів з БА порівняно з контрольною групою, що свідчить на користь залучення їх до патогенезу БА у дітей. Ключові слова: бронхіальна астма, система детоксикації, ген b2-адренорецептора, поліморфізм, комбінований генотип. Цель. Исследовать ассоциацию полиморфных вариантов генов ферментов первой – CYP1A1 (T6235C) и второй – NAT2 (С481Т, G590A, G857A), GSTM1 («0»), GSTT1 («0») и GSTP1 (A313G) фаз системы детоксикации, а также гена ADRB2 (C79G) с развитием бронхиальной астмы (БА) у детей. Методы. Полиморфные варианты изучали с помощью ПЦР и ПДРФанализа у 86 здоровых индивидов и 114 пациентов с клиническим диагнозом БА. Результаты. Установлена частота полиморфных вариантов генов ферментов первой и второй фаз системы детоксикации, а также гена ADRB2 у больных БА детей и здоровых индивидов. Выводы. Полиморфные варианты генов NAT2 (481Т), GSTP1 (313G) и ADRB2 79G и их комбинации в генотипе чаще наблюдаются среди пациентов с БА по сравнению с контрольной группой, что свидетельствует в пользу их вовлечения в патогенез БА у детей. Ключевые слова: бронхиальная астма, система детоксикации, ген b2-адренорецептора, полиморфизм, комбинированный генотип.